Assessing Gallo-Roman mobility at the Rue Jacques Brel necropolis site (1st to 3rd c. CE), France. (June 2022) - Stark, Robert J.; Emery, Matthew V.; Schwarcz, Henry; Castex, Dominique; Prowse, Tracy L.
Highlights: δ 18 O and 87 Sr/ 86 Sr values were used to assess mobility at Rue Jacques Brel necropolis. Bagplot analysis of δ 18 Odw and 87 Sr/ 86 Sr values did not identify any distinct outliers. Mobility at Gallo-Roman Rue Jacques Brel appears evident to a limited degree. Regions of isotopic value homogeneity remain a challenge for assessing mobility. Rue Jacques Brel brings forth questions about mobility in Imperial Roman provinces. Abstract: Arguably one of the key elements that would come to define Roman society, mobility played a primary role in the expansion and maintenance of Roman authority. With the acquisition of ever- expanding territory and the establishment of new provinces came opportunities for both outward mobility from the Roman heartland as well as immigration to Rome. Discussions of mobility within the Roman empire typically focus on contexts from Rome proper and surrounding regions, while comparatively less is known regarding mobility in the provincial territories. The study presented herein utilises δ 18 O values from the second molar (M2) dental enamel of 39 adults, 20 of whom were additionally analysed for 87 Sr/ 86 Sr, to assess for potential mobility events among individuals interred in the ca. 1st to 3rd c. CE Gallo-Roman necropolis of Rue Jacques Brel in the Aquitaine region of France. Located in the modern-day municipality of Saintes, Jacques Brel functioned as a manufacturing location on the periphery of Mediolanum Santonum, the capital of Roman Aquitaine. While several individuals have isotope values that fall outside of the expected local δ 18 Odw and 87 Sr/ 86 Sr ranges, suggesting mobility events, combine bagplot analysis of δ 18 Odw and 87 Sr/ 86 Sr did not identify any distinct outliers, bringing into question the nature of mobility to the site of Rue Jacques Brel. The small proportion of individuals identified as non-local among the individuals sampled from the Rue Jacques Brel necropolis raises several questions regarding the nature of mobility within Roman provincial settings and implications of site size and function on mobility. Lay summary: One of the main questions about living in the Roman empire was "who was mobile?" With such a large territory covered by the Roman empire there were many opportunities to move from place to place, with some of the most common reasons for moving resulting from military deployment, government administration positions, and business ventures. Among the studies conducted to date, a significant number have focused on mobility to the capital of Rome itself, while fewer studies have looked directly at mobility in provincial contexts. The study presented here focusses on mobility to a provincial site in western France, a short distance from Bordeaux, called Rue Jacques Brel Necropolis. This site was the location of a small manufacturing operation and has an associated cemetery. Using statistical analyses of chemical data, it was possible to gain insights to potential mobility among the individuals interred in this cemetery. Of 39 individuals investigated, only a small number appeared truly non-local to the area of Rue Jacques Brel. Additional statistical analysis did not identify any distinct outliers, which brings forth several questions about approaches to gauging mobility. Numerous questions remain to be further investigated to help clarify these initial observations.